2020
DOI: 10.1021/acsami.0c17338
|View full text |Cite
|
Sign up to set email alerts
|

MXene-Modulated Electrode/SnO2 Interface Boosting Charge Transport in Perovskite Solar Cells

Abstract: Interface engineering is imperative to boost the extraction capability in perovskite solar cells (PSCs). We propose a promising approach to enhance the electron mobility and charge transfer ability of tin oxide (SnO2) electron transport layer (ETL) by introducing a two-dimensional carbide (MXene) with strong interface interaction. The MXene-modified SnO2 ETL also offers a preferable growth platform for perovskite films with reduced trap density. Through a spatially resolved imaging technique, profoundly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 61 publications
2
69
0
Order By: Relevance
“…[ 1–4 ] The power conversion efficiency (PCE) of lead (Pb) based perovskite solar cells (PVSCs) has surged to certified 25.5%, continuously approaching their Shockley‐Queisser (SQ) limit efficiency, which makes it strongly competitive for the next generation of photovoltaic technology. [ 5–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–4 ] The power conversion efficiency (PCE) of lead (Pb) based perovskite solar cells (PVSCs) has surged to certified 25.5%, continuously approaching their Shockley‐Queisser (SQ) limit efficiency, which makes it strongly competitive for the next generation of photovoltaic technology. [ 5–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al reported a perovskite solar cell with a thin Ti 3 C 2 T x MXene layer inserted between the F-doped SnO 2 (FTO) electrode and the SnO 2 ETL [ 79 ], and Fig. 8 g, i shows the architecture and cross-sectional SEM image of the device.…”
Section: Applications Of Mxenes In Solar Cellsmentioning
confidence: 99%
“…In 2020, Wang et al, reported a champion stabilized PCE of 20.65% with a V OC of 1.11 V and highly improved J SC of 24.34 mA·cm −2 , by introducing a thin layer of Ti 3 C 2 T x MXene between the SnO 2 ETL and electrode of PSC [ 84 ]. As can be seen from Figure 7 f, the introduction of Ti 3 C 2 T x MXene layer between SnO 2 ETL and electrode optimized the conduction band alignment, resulting in improved charge transfer kinetics and better performance.…”
Section: Applications Of Mxenes In Pscsmentioning
confidence: 99%